2016
DOI: 10.3892/etm.2016.3993
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to lymphocyte ratio is associated with the severity of coronary artery disease and clinical outcomes of percutaneous coronary intervention in the Chinese Han population

Abstract: Abstract. The aim of the present study was to evaluate whether the ratio of the absolute number of platelets to the number of lymphocytes (PLR) correlates with the severity of coronary artery disease (CAD) and major adverse cardiovascular disease (CVD) events in Chinese patients with CAD. PLR was calculated as follows: PLR=platelet count/lymphocyte count, using the complete blood counts of 854 Chinese Han subjects. CAD severity was determined using angiographic evidence by cardiologists unaware of the study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 34 publications
5
39
0
2
Order By: Relevance
“…[8] PLR may act as an effective biomarker to predict CVD and the risk of future CVD events. [10] In our study, we found that as the mean PLR increased, the stenosis grade also increased. The mean PLR level in the control group was lower than in the patient group, but there was no statistical significance.…”
Section: Discussionsupporting
confidence: 49%
“…[8] PLR may act as an effective biomarker to predict CVD and the risk of future CVD events. [10] In our study, we found that as the mean PLR increased, the stenosis grade also increased. The mean PLR level in the control group was lower than in the patient group, but there was no statistical significance.…”
Section: Discussionsupporting
confidence: 49%
“…Our best cutoff value of PLR with a high degree of specificity but fairly low sensitivity was 159; of note, PLR > 150 was associated with an odds ratio of 1.9 for critical limb ischemia in patients with peripheral arterial disease . In addition, preoperative PLR > 142 was observed in coronary patients with post‐coronary bypass grafting complications, PLR > 128 was an independent predictor of future events in patients with NSTEMI, and PLR > 171 in patients with stable CAD was associated with more severe coronary disease and worse prognosis . PLR is, therefore, a novel parameter which indicates inflammation and carries prognostic significance in a variety of clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al in their study showed that PLR is independently associated with CAD severity and long-term major adverse CVD events. This might explain higher incidence of mortality in our patients with higher PLR [12].…”
Section: Discussionmentioning
confidence: 75%